Comparative analysis of product distribution and kinetics in steam gasification of rice straw under atmospheric and pressurized conditions - Deming Zhang; Mingshui Ma; Hao Bai; Rui Zhou; Zhenguo Li; Yiqing Yao (Biomass and Bioenergy, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Genomic characterization of historical Jinlingnan individuals: insights into genetic continuity and trans-Eurasian signals in eastern China - Shuyi Li; Yuchun Wang; Qu Shen; Jinguo Zan; Mengying Han; Zishuai Huang; Rui Wang; Xinyi Wang; Haifeng He; Le Tao; Hao Ma; Kongyang Zhu; et al. (Human Genetics, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Organic amendments induce crop-specific soil biotic homogenization associated with SOC sequestration: Evidence from a 35-year intercropping experiment - Guizong Zhang; Jiudong Zhang; Rui-Peng Yu; Hao Yang; Xingguo Bao; Wenju Liang; Qi Li; Long Li (Soil and Tillage Research, 2026)

Identification and transcriptional analysis of eight C1q genes in Takifugu obscurus during bacterial infection - Hao Wu; Ding-Yi Chen; Xiao-Han Li; Rui Shen; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

Built-in electric field for synergistically regulating electronic structure and interfacial hydrogen-bond network toward ampere-level current anion exchange membrane water electrolysis - Yujie Liang; Xinyu Lao; Jiaying Zhang; Hao Feng; Rui Min; Jingjing Wang; Yingying Zheng; Jiaqi Pan; Chaorong Li; Jun Cao (Chemical Engineering Journal, 2026)

A review of the mechanism, modification strategies and recent advances of piezocatalysis - Ying Cheng; Yue Cheng; Sa Li; Weichang Hao; Rui Guo (Journal of Environmental Chemical Engineering, 2026)

Electronic, optical and mechanical properties, and photocatalytic water splitting of Janus ZrHfCO2 under biaxial strain: First-principles prediction - Rui-Wen Yan; Hao Zhang; Xiao-Hong Li; Rui-Zhou Zhang; Hong-Ling Cui (Journal of Environmental Chemical Engineering, 2026)

Electrospun films prepared by incorporating modified ZnO nanoparticles-stabilized Pickering emulsions into polyvinyl alcohol and chitosan for active antibacterial packaging - Hao Wang; Ziyi Li; Hui Li; Lingna Meng; Rui Bai; Simin Li; Haibei Chi; Yuxing Xu (Food Research International, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

How plant diversity and nitrogen deposition affect the net nutrient retention on temperate extensive green roofs: A case study - Guang Hao; Yihan Wang; Hechen Li; Shaobo Gao; Runze Wu; Zhuolin Li; Jiale Han; Hongyuan Li; Rui Hua; Nan Yang (Ecological Engineering, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Bone biochar as a bifunctional catalyst for sustainable co-removal of nitrate and phosphate in constructed wetlands - Tao Liu; Hao Qin; Sihan Li; Gongliang Zhang; Rui Wang; Yi Sun; Haihua Wu; Yuxin Zeng; Yi Chen (Water Research, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Thaw slump susceptibility assessment in the central Qinghai–Tibet Plateau permafrost region based on an interpretable 2D-CNN framework with SBAS-InSAR deformation - Yuting Yang; Rui Wang; Chen Liu; Xia Hu; Jifu Liu; Lianyou Liu; Xiaoyan Li; Hao Zheng (Journal of Hydrology, 2026)

Divergent effects of biodegradable and conventional microplastics on denitrification in soils: Mechanisms governing N₂O emission and product stoichiometry - Hao Zhang; Xiao Li; Minhang Zhu; Rui Wang; Jinbo Zhang; Christoph Müller; Rui Jiang (Journal of Hazardous Materials, 2026)

Environmentally relevant imidacloprid exposure elicits hippocampal microglial apoptosis via JNK-FOXO3 pathway: Implication for latent central neurotoxicity - Xinyi Wen; Meiyan Li; Zhongyuan Zhang; Jingwen Wang; Hao Hu; Weihong Wang; Jing Jin; Kairong Wang; Jian Sun; Rui Zhang (Journal of Hazardous Materials, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Stress-homogenized and solvation-regulated biomass hydrogel inducing Zn (101) epitaxial growth for ultra-stable anodes - Aoxue Lang; Yongfa Huang; Tingzhen Li; Rui Zhong; Linxuan Su; Zhendong Liu; Jianyun Gan; Ren Zou; Yuan He; Emmanuel Iwuoha; Usisipho Feleni; Kasim Ocakoglu; et al. (Chemical Engineering Journal, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Surface phosphate functionalization regulates electron polaron and glycerol oxidation pathway for dihydroxyacetone production over BiVO4 photoanodes - Songying Qu; Baiyi Li; Mingcong Wang; Zhanghong Zhou; Rui Zhao; Hao Wu (Chemical Engineering Journal, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Spatiotemporal dynamics of land degradation in the three gorges reservoir area and its coupling mechanisms with biodiversity and human activity intensity - Cuicui Ji; Hao Cui; Rui Ma; Dandan Ke; Xia Li; Fenglei Han; Xizeng Huang; Jie Liu; Gang Yang; Liejian Wang (CATENA, 2026)

Effects of Compound Yeast Culture on the Intestinal Morphology, Intestinal Function, and Microorganisms of Weaned Lambs - Shixiong Liu; Puguo Hao; Hui Chen; Xueqiang Li; Xiaohui Xu; Rui Du; Chen Xue; Lan Yang; Dacheng Liu (Probiotics and Antimicrobial Proteins, 2026)

An energy-spectrum-biased auto-importance sampling method for variance reduction in Monte Carlo energy spectrum simulations - Yang Zhou; Hui Zhang; Zhen Wu; Yisheng Hao; Rui Qiu; Jiajun Wu; Jiahe Shang; Junli Li (Annals of Nuclear Energy, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

The Matthew effect of defects in microflowers CuS/carbon foam composite optimizes the dielectric response for high-performance microwave absorption - Weibin Deng; Tiehu Li; Arooba Kanwal; Hao Li; Alei Dang; Keke Li; Peng Chang; Rui Zhou; Shengtao Gao; Yating Zhang; Hongjing Wu (Chemical Engineering Journal, 2026)

Microbial inoculation in green roofs: progress, challenges and ecological regulation strategies - Nan Yang; Hechen Li; Yihan Wang; Pingrui Jiang; Shaobo Gao; Hongyuan Li; Rui Hua; Xinjian Shi; Guang Hao (Urban Ecosystems, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Diameter-independent indices for TBM rock-mass classification - Xiu-xiu Cao; Xu Li; Li-jie Du; Yu-zhi Zhang; Hao Cai; Yun-pei Zhang; Rui-lang Cao (Tunnelling and Underground Space Technology, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Distinct differences of rice grain quality caused by developmental stage and cultivar: A widely targeted metabolomics perspective - Xuexia Yuan; Pingxiang Liu; Rui Gao; Jingxiu Bi; Tong Zhao; Haining Hao; Xia Li; Yutao Wang (Food Chemistry, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Dynamic trajectories of health-related quality of life during neoadjuvant chemotherapy in breast cancer: differential effects of anthracycline-taxane sequencing - Yuanyuan Wang; Ye Wang; Hao Yao; Jingjing Ding; Yichun Gong; Junhan Li; Danni Shen; Rui Chen; Jue Wang; Xiaoming Zha (Science China Life Sciences, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

P2Y12-AMPKα2 signaling contributes to cardiomyocyte senescence in doxorubicin-induced heart failure - Qianqian Niu; Huidan Wang; Mengyao Zhao; Hongdou Zhang; Rui Hao; Peiyao Liu; Lijuan Guo; Bulei Chen; Yuting Xi; Peng Li; Yaling Yin (Molecular and Cellular Biochemistry, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Genome-wide association study of wheat (Triticum aestivum L.) starch pasting properties - Jiahui Jiang; Hao Chang; Yongji Ma; Rui Jin; Rui Yu; Zhenhua Lu; Tianqi Bai; Yufeng Xu; Ruili Gou; Chengyu Lian; Wenting Zhang; Yingang Hu; et al. (Journal of Cereal Science, 2026)

Accessory minerals constrain anatexis and melt extraction in deep crust and implications for granite genesis - Wenxiang Zhang; Yujie Zhao; Bin Fu; Guangyan Zhou; Hao Wang; Rui Li; Zhaochu Hu; Yuanbao Wu (Geochimica et Cosmochimica Acta, 2026)

Gallic acid-modified starch conjugates inhibit harmful aldehydes in fried battered fish: Based on structural characterization and antioxidant activity - Ying Li; Hao Zhang; Jiamu Kang; Meng Yang; Hanyu Liu; Wuyun Chen; Tingting Zhang; Deming Quan; Rui Zhang; Yuan Xia; Xin Du; Xiufang Xia (Food Research International, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

Position dependent elasticity of the anterior talofibular ligament in healthy young women: an in-vivo shear wave elastography study - Zili Chen; Wan Zhou; Hao Liang; Xing Liu; Yibo Li; Li Yang; Huijuan Xiang; Rui Du (European Journal of Applied Physiology, 2026)

Multivariate distribution modeling and cross-correlation spatial variability stochastic characterization for mechanical properties of marine clay - Hao Li; Rui Liu; Lipeng Liu; Tao Wang; Guoqing Zhou (Ocean Engineering, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Biotransport and biotransformation of arsenic in earthworm tissues: Advancing vermiremediation strategies of soil contamination - Yunxiang Xu; Muyuan Wang; Yizhao Wu; Yifan Zhang; Rui Jiang; Qi Zhao; Jibao Jiang; Hao Qiu; Yinsheng Li (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Data-driven assessment of nitrogen and phosphorus buffering capacity across 460 Chinese watersheds: Spatial patterns, drivers, and future projections - Yunfei Cao; He Yao; Chuang Zhang; Chaojun Gu; Lin Yang; Rui Hao; Xiao Li; Zhen Wang; Haibing Xiao; Jian Wang; Zhihua Shi (Water Research, 2026)

Resilience assessment and enhancement of regional transportation system - Honghai Li; Rui Hao; Bin Yu (Journal of Transport Geography, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Evolution of groundwater nitrate during managed aquifer recharge: Insights from DOM characteristics and stable isotopes - Congchao Xu; Rui Li; Weiwu Hu; Liting Hao; Bowen Shi; Tianyu Zhang; Chuanping Feng; Nan Chen (Journal of Hazardous Materials, 2026)

Ecosystem vertical structural complexity and soil nutrition synergistically enhance extreme drought resistance via water use efficiency in the Yangtze River Basin - Yue Cao; Xinyi Hao; Fei Yu; Rui Wang; Huiwen Li (Journal of Environmental Management, 2026)

Study on physicochemical properties and light-controlled antibacterial activity of side-by-side nanofiber films prepared by dual-channel electrospinning system - Hao Wang; Lingna Meng; Hui Li; Ziyi Li; Simin Li; Rui Bai; Haibei Chi; Xiaoge Wang (Food Research International, 2026)

Integrated design of thermally actuated metastructure for modulatable dual vibration isolation function - Yue Hu; Jianlei Zhao; Hao Zhou; Ivana Kovacic; Runan Hua; Honggang Li; Rui Zhu (Engineering Structures, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Faecalibacterium prausnitzii derived postbiotic attenuates PEDV-induced mitochondrial apoptosis through blocking viral entry - Lingcong Deng; Rui Luo; Shihan Yang; Letian Li; Nan Li; Yu Dong; Jiayi Hao; Ju Li; Anqi Deng; Xueyan Ai; Maopeng Wang; Chang Li (Veterinary Microbiology, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Research on HaNRX, a potential RNAi target gene in Helicoverpa armigera - Rui Han; Dongdong Chu; Zhibin Hao; Haichao Li; Xuexia Miao; Shiheng An; Ruobing Guan (Pesticide Biochemistry and Physiology, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Robust oxygen vacancy surfaces induce chemical bonding interfaces of Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction with asymmetric adsorption sites for efficient photocatalytic nitrogen fixation - Yongli Li; Xin Kong; Rui Bao; Liang Liu; Zhenhua Ge; Feng Liu; Hao Cui; Jianhong Yi (Chemical Engineering Journal, 2026)

Corrigendum to “Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells” [Bioresour. Technol. 443 (2026) 133815] - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

Multifunctional deep learning-based mechanical-laser collaborative adaptive precision weeding system for lettuce - Rui Hu; Lei Kong; Wen-Hao Su; Bo-Wen Dong; Yujin Wang; Xiaobin Li; Yankun Peng (Computers and Electronics in Agriculture, 2026)

Suffusion in shield tunnel surrounding soils under train vibration using an improved DEM-PNM coupling method - Si-Rui Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Zhao-Geng Chen; Hui-Hao Chen; Hai-Yun Li (Tunnelling and Underground Space Technology, 2026)

Species delimitation within a taxonomically complex group: An example from the genus Apodemus (Rodentia: Muridae) - Xuan Pan; Buqing Peng; Xuming Wang; Zhongzheng Chen; Hao Cheng; Rui Liao; Chia-Lung Huang; Jiatang Li; Shaoying Liu (Molecular Phylogenetics and Evolution, 2026)

The enhanced role of formic acid on sulfuric acid-ammonia-driven nucleation in forest regions and polluted city areas - Shasha Chen; Rongrong Li; Chengyan Zhang; Shuqin Wei; Rui Wang; Biwu Chu; Xiaomeng Zhang; Hao Li; Tianlei Zhang (Journal of Environmental Sciences, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Quantifying the impact of vegetation greenness change on surface urban heat islands across 133 major cities of China - Rui Yao; Zhihao Zhang; Wenjie Li; Hao Li; Shiya Zhu; Hongji Zhu; Chuan Wang; Dewei Luo; Ying Yang; Junli Li; Weitao Han; Xin Huang (Environmental Research, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Heterogeneous typing of physical-mental symptoms in stroke patients during recovery phase based on latent class analysis and influencing factors - Li Cao; Rui Song; Bingying Zhai; Zihan Zhang; Xiao Zhang; Yuying Hao (Neurophysiology, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Enhanced rock-breaking performance of an angular Helmholtz cavitation jet nozzle: Flow field dynamics and mechanism analysis - Chenrui Guo; Rui Li; Hao Wang; Zhongwei Huang; Gensheng Li; Huan Li; Jingbin Li; Jiaqing You (Process Safety and Environmental Protection, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Comprehensive performance of iron-loaded biochar adsorption of U(VI) at an industrial scale based on life cycle assessment and economic analysis - Jia He; Zhou Shen; Yisa Li; Hao Wen; Rui Lu; Shaoli Fan; Jian Gao (Environmental Research, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Expression of Beta vulgaris betaine aldehyde dehydrogenase 1 (BvBADH1) confers salt tolerance in tobacco (Nicotiana benthamiana) - Ming Wei; Xiang-Yu Chen; Meng-Li Li; Hao Li; Xin-Rui Wu; Guo-Qiang Wu (Physiology and Molecular Biology of Plants, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Integrated assessment reveals plowing/no-tillage rotation as the trade-off considering crop yield and environmental performance in the Loess Plateau - Xingyu Guo; Shulan Wang; Hao Wang; Naeem Ahmad; Xiaoli Wang; Jun Li; Rui Wang (Agricultural Systems, 2026)

Low-thrust transfers to halo orbits in different systems: Hybrid optimization and free-coast design - Zhaoyu Li; Tianyou Li; Hao Zeng; Rui Xu (Advances in Space Research, 2026)

Correction: Lei et al. Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus. Fishes 2024, 9, 452 - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2025)
In the original publication [...]

The Eocene blueschist in Zeyarat metamorphic complex, Iranian Makran: Implication for subduction dynamics in plates interface - Zhou Tan; Wenjiao Xiao; Rasoul Esmaeili; Parisa Gharibnejad; Miao Sang; Qigui Mao; Hao Wang; Rui Li; Zhiyong Zhang; Jien Zhang (Lithos, 2025)

Synergistic KOH/MgSO₄ activation of hazelnut shell biochar: Tailored hierarchical porosity and surface chemistry boosting high-efficiency capacitive deionization - Shumin He; Youzhao Wang; Xiaolong Gao; Jiedong Hao; Enbo Zhang; Rui Du; Tengfei Li; Yaonan Zhu; Tong Zhu (Journal of Environmental Chemical Engineering, 2025)

Retention-driven water flow regulation: A network perspective - Xuan Jiang; Jinsong Zhao; Zhiwen Cai; Jiating Li; Jian Wang; Ling Wang; Xiao Li; Rui Hao; Shuxia Yu; Zhihua Shi (Journal of Environmental Management, 2025)

Location-specific climate and environmental benefits of China’s coal mining phase-down towards carbon neutrality - Hao Li; Tao Yang; Linman Li; Bin Lu; Tianzheng Zhang; Xiaolong Lu; Rui Peng; Zhaohua Wang (Global Environmental Change, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Quantifying the relative importance of factors influencing rainfall partitioning in a rainfed apple orchard - Rui Zhang; Li Wang; Hao Liu (Hydrological Sciences Journal, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Prevalence and risk factors of Giardia duodenalis in sheep and goats in global: A systematic review and meta-analysis - Zhengyi Li; Wei Wei; Yuan Ma; Luyao Hao; Yuan Guo; Rui Wang (Preventive Veterinary Medicine, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Simple and economical photoelectrode modification for efficient ranitidine removal: Improved surface reactivity and switchable radical/non-radical pathways - Jiajun An; Yanan Li; Lei Wang; Jiajin Hao; Lujie Nie; Bo Gao; Xudong Wang; Jin Wang; Rui Miao; Miaolu He; Danxi Huang (Journal of Hazardous Materials, 2025)

Enhancing NO3− reduction on BiFeO3/Cu cathode via ferroelectric polarization: A novel strategy for surface electronic structure regulation - Hao Chen; Houfen Li; Yue Zhao; Yunlong Ma; Zhichao Liu; Rui Li; Sufang Wang; Aijuan Zhou; Xiuping Yue; Haibing Meng; Hongtao Yu; Xu Zhao (Journal of Environmental Management, 2025)

Environmentally friendly, lightweight, and recyclable nanocomposite foams for sustainable electromagnetic interference shielding via integrating a dynamically crosslinked biobased polyamide system with supercritical carbon dioxide foaming - Chia-Hsing Lin; Chia-Wei Lee; Lyu-Ying Wang; Rui-Hao Li; Yi-Huan Lee (Chemical Engineering Journal, 2025)

Corrosion-resistant TiZrNbTaW high-entropy alloy coatings for Ti anode polar plates of proton exchange membrane water electrolyzers - Hongwu Zhao; Rui Gao; Hao Li; Muyu Ma; Guoxing Chen; Daiman Zhu; Marcos Antonio Coelho Berton; De Ning; Anke Weidenkaff; Yongli Li (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Electrospun Mn-doped ZIF-67 composite nanofibers with high water stability for efficient adsorption of antibiotics in aqueous systems - Xiaolin Yue; Can Cui; Shaolin Deng; Lan Wang; Ping Li; Anhong Li; Yizhong Zhang; Rui Hao; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Enhancing Cannabidiol Apparent Solubility and Oral Delivery: Self-assembled Nanomicelles of Amphiphilic Block Copolymer with γ-Polyglutamic Acid-grafted Cholesterol - Rui Li; Wenhui Ruan; Liyan Lu; Zhijuan Wu; Rui Hao; Yingli Wang; Jue Chen (Pharmaceutical Research, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Unsupervised domain adaptation semantic segmentation method for wheat disease detection based on UAV multispectral images - Yuchen Zhang; Xingan Hao; Feilong Li; Zexi Wang; Dongxiang Li; Mei Li; Rui Mao (Computers and Electronics in Agriculture, 2025)

Emerging MXene-based Composites: Synthesis, and Recent Advances in Food Contaminant Analysis - Mengmeng Gao; Rongchao Li; Huilin Li; Xiaochun Hu; Jingming Sun; Hao Wang; Rui Gao; Huilin Liu; Mingfei Pan; Shuo Wang (Trends in Food Science & Technology, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Holographic, traceable, and switchable anti-counterfeiting using temperature-tolerant relief gratings on polyimide substrate - Chengwei Xiao; Haixian Shi; Hao Zhong; Chengbin Zou; Yiyong Chen; Jinru Li; Weien Liang; Wanying Zhang; Dezhi Zhan; Shilong Zhong; Rui Chen; Zhaoxiang Zhu; et al. (Chemical Engineering Journal, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Kinematic mechanisms of coordinated fore and hind hoof movements for stability enhancement and energy efficiency in reindeer long-distance migration - Kaixiang Chen; Rui Zhang; Wenchao Dong; Hao Pang; Guoyu Li; Lige Wen (Polar Biology, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Effect of Drought Stress on Root Metabolome and Soil Microbial Characteristics for Maize (Zea mays L.) Seedlings - Rui Hao; Hao Li; Shufang Qin; Wenquan Chen; Qiuchen Guo; Yanan Huang; Xiaohong Chen; Yajun Li (Current Microbiology, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Coaxial emulsion electrospinning fiber films loaded with OEO for active packaging of pork - Hao Wang; Rui Ren; Mengjiao Li; Zhennan Gao; Hui Li; Simin Li (Food Research International, 2025)

Developing a Cas12a-based detection method on the emetic Bacillus cereus strains in infant formulas - Hao Wang; Rui Yin; Yingying Huang; Yan Li; Min Yue (Food Research International, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Key role of macrophyte-dominated habitats over cyanobacteria-dominated habitats in stability of microbial sulfur cycling in freshwater lakes - Rui-Ze Li; Zhi-Jie Zhu; Xing-Hao Li; Yi-Ying Jiao; Li-Ya Zhao; Zhao-Hua Li; Mo Chen (Environmental Research, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

2D nonlayered titanium oxynitrides intercalated with nitrogen-doped graphene for pseudocapacitive energy storage - Xiuli Li; Rui Huo; Zihuan Tang; Yulei Ren; Hao Song; Paul K. Chu; Kaifu Huo (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

Streptococcus suis AdcA interacts with factor H and inhibits C3b deposition on the bacteria to participate in complement evasion - Siqi Pang; Zhulin Qiao; Jiajia Xu; Hao Tang; Qiuhong Zhang; Weiyao Han; Lu Peng; Jiaojiao Yang; Jiao Zhang; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Corrigendum to “Infection mechanisms of Pochonia chlamydosporia: A breakthrough in Fasciola hepatica egg control” [Vet. Parasitol. 337 (2025)110463] - Luyao Hao; Hongyou Liu; Fengmiao Zhao; Yuan Ma; Zhengyi Li; Rui Wang (Veterinary Parasitology, 2025)

Infection mechanisms of Pochonia chlamydosporia: A breakthrough in Fasciola hepatica egg control - Luyao Hao; Hongyou Liu; Fengmiao Zhao; Yuan Ma; Zhengyi Li; Rui Wang (Veterinary Parasitology, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Transcriptomics and Metabolomics Analysis Reveal the Mechanism of Hormones Regulation of the Flower Bud Formation and Development in Phalaenopsis Orchid - Xiaofen Gao; Yang Hao; Xiaoying Yang; Yanping Shi; Li Zhang; Rui Yan (Journal of Plant Growth Regulation, 2025)

Cerebellar large-scale network connectivity in Parkinson’s disease: associations with emotion, cognition, and aging effects - Chentao He; Zhenzhen Chen; Mengfei Cai; Piao Zhang; Hao Li; Xi Chen; Qi Qi; Rui Yang; Yan Li; Zaiyi Liu; Lijuan Wang; Yuhu Zhang (Brain Imaging and Behavior, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

The antioxidant protein PntA coordinates with OmpW to resist oxidant stress in Actinobacillus pleuropneumoniae - Weiyao Han; Qiuhong Zhang; Zhen Luo; Hao Tang; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Electronic structure modulation and substance transfer acceleration induced by synchronous construction of a tri-functional electrocatalyst with host–guest role swapping in zinc-air batteries - Liping Hao; Tao Yu; Xiaomao Liu; Jinsheng Li; Rui Guo; Xuanwen Liu; Sihan Chen; Chunming Liu (Chemical Engineering Journal, 2025)

Preparation of sodium alginate antibacterial porous composite pads embedded with centrifugally spun nanofibers by freeze-drying and recasting for active food packaging - Hao Wang; Mengjiao Li; Rui Ren; Zhennan Gao; Lingna Meng; Ziyi Li; Chuanai Cao (Carbohydrate Polymers, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Identification and fungicide sensitivity of Fusarium oxysporum, the cause of Fusarium wilt on Codonopsis pilosula in Shanxi Province (Lu Dangshen), China - Yan Wang; Dainan Hao; Haozhe Jiang; Zhaoxiong Fei; Rui Zhao; Jiaxin Gao; Guangxin Li; Chunwei Wang (Crop Protection, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Field test of geosynthetic-reinforced floating pile-supported embankments on soft soil - Rui Rui; Shi-kai He; Long-fan Peng; S.J.M. Van Eekelen; Liang-hao Li; Yu-qiu Ye (Geotextiles and Geomembranes, 2025)

Corrigendum to “Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation” [Food Research International 203 (2025) 115792] - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Correlation of lipid hydrolysis, oxidation, and molecular transformation with volatile compound revolution in pork during postmortem wet-aging process - Kaihua Zhang; Rui Hao; Shouwei Wang; Zheqi Zhang; Dan Li; Xiaoman Li; Bing Zhao; Shunliang Zhang; Yan Zhao; Xiangning Chen (Food Chemistry, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Ratio Fluorescence Sensor Based on Bimetal MOFs for the Detection of Hg2+and H2O2 - Bo-Ming Han; Hao-Rui Zhang; Wen-Jie Gao; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Fluorescence, 2025)

Detecting wheat yellow dwarf disease by employing a Dual-Branch multiscale model from UAV multispectral images - Xingan Hao; Zexi Wang; Yuchen Zhang; Feilong Li; Meili Wang; Jialin Li; Rui Mao (Computers and Electronics in Agriculture, 2025)

Vertical migration characteristics of polychlorinated biphenyls (PCBs) in estuarine and coastal zones under complex environmental conditions - Rui Pan; Nan Zhang; Jiqing Li; Xiao Xiao; Hao Wu; Xianzhang Dang; Shuya Hu (Marine Pollution Bulletin, 2025)

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

Insight into resistance relaxation characteristics of proton exchange membrane fuel cell in purge operation: Experiment, application, and mechanisms - Yuqing Li; Hao Yuan; Xueyuan Wang; Xuezhe Wei; Jiangong Zhu; Rui Ma; Lei Gao; Haifeng Dai (Journal of Cleaner Production, 2025)

Amelioration of myofibrillar protein emulsion gel properties by mildly oxidized sunflower oil - Jinyang Chang; Rui Liu; BeiBei Zheng; Xinzhu Gao; Baorui Li; Ye Zhang; Tianxin Wang; Hao Wang (Food Chemistry, 2025)

Microbial community structure and water quality performance in local scrubber reclaim system for water reclamation of the semiconductor industry: A case study of a semiconductor plant in Beijing - Yu-Di Li; Yin-Hu Wu; Hao-Bin Wang; Rui-Ning Wang; Pei-Hua Li; Bang-Hao Huang; Hong-Ying Hu (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A new oviraptorosaur from the Lower Cretaceous Miaogou Formation of western Inner Mongolia, China - Mingze Hao; Zhiyu Li; Zhili Wang; Shuqiong Wang; Feimin Ma; Qinggele; J. Logan King; Rui Pei; Qi Zhao; Xing Xu (Cretaceous Research, 2025)

Antagonistic activity of Pochonia chlamydosporia against three helminth eggs and characterization of its serine protease - Luyao Hao; Fengmiao Zhao; Yuan Guo; Yuan Ma; Zhengyi Li; Wen Wang; Hongliang Luo; Rui Wang (Veterinary Parasitology, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Non-steady flow decomposition behaviors of heat and mass transfer on intrinsic kinetics for methane hydrate particles transported in pipelines - Xinfu Liu; Chunhua Liu; Qingping Li; Zhongxian Hao; Rui Qin; Haiyuan Yao; Ming Li; Zunzhao Li (Fuel, 2025)

Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Erroneous Differentiation of Tendon Stem/Progenitor Cells in the Pathogenesis of Tendinopathy: Current Evidence and Future Perspectives - Yucheng Gao; Hao Wang; Liu Shi; Panpan Lu; Guangchun Dai; Ming Zhang; Bowen Han; Mumin Cao; Yingjuan Li; Yunfeng Rui (Stem Cell Reviews and Reports, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

Reversible multilevel stimuli-responsiveness and multicolor room temperature phosphorescence to fluorescence transition based on a metal–organic framework system - Hui-Li Sun; Zhong-Hao Wang; Rui-Qi Huang; Zhuo-Di Chen; Mei Pan (Chemical Engineering Journal, 2025)

Highly active and CO-resistant PdRuMo/C with a wide potential-stable window toward alkaline hydrogen oxidation reaction - Chunxiao Chai; Haoliang Huang; Hao Yang; Jiaqi Qin; Chongyun Sun; Yongpeng Li; Zhaoqi Wang; Xinwei Zhao; Zhongyu Qiu; Tiantian Li; Jiahuan Li; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

ε-Poly-L-lysine/rhamnolipid bifunctional coating based on green electrostatic assembly technology for fruit packaging and preservation - Quanfei Li; Qian Chen; Kai Yang; Hao Liu; Delei Xu; Yian Gu; Liang Sun; Peng Lei; Rui Wang; Hong Xu (Chemical Engineering Journal, 2025)

A combined strategy of brain neuroprotection and endogenous neuroregeneration for enhanced intracerebral hemorrhage treatment via an injectable biomimetic hydrogel with efficient ROS scavenging and therapeutics delivery - Jiake Xu; Luyao Wan; Xueqi Wang; Yang Wei; Yinhai He; Shenglan You; Rui Zhong; Chengwei Wang; Hao Li; Chao You; Meng Tian (Chemical Engineering Journal, 2025)

Identifying the Pathogenicity of a Novel NPRL3 Missense Mutation Using Personalized Cortical Organoid Model of Focal Cortical Dysplasia - Rongrong Lu; Ying Xu; Hao Li; Man Xiong; Wenhao Zhou; Weijun Feng; Rui Zhao (Journal of Molecular Neuroscience, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Ultrabright silicon nanoparticles combined with o-phenylenediamine for ratiometric fluorescence and smartphone imaging dual-mode detection of nitrite - Wen-Jie Gao; Ming-Yue Tian; Xing-Hui Ren; Hao-Rui Zhang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Hazardous Materials, 2024)

Endogenous phosphorus release from plateau lakes responds significantly to temperature variability over the last 50 years - Chao Yan; Rui Xia; Yan Chen; Lixin Jiao; Xiaoyu Liu; Yingze Yin; Qiang Hu; Kai Zhang; Lina Li; Hao Liu (Journal of Environmental Management, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

Exceeding the theoretical limit of interfacial evaporation efficiency by using the carbon-based aerogel evaporator with cold evaporation surface - Rui Yang; Xiaoke Li; Wei Xie; Size Zheng; Hao Shi; Jinwen Shi; Dengwei Jing (Desalination, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Exploring retinal degenerative diseases through CRISPR-based screening - Rui Li; Fengming Yang; Boling Chu; Dehua Kong; Jing Hu; Hao Qian (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Parasitic infestations present significant threats to the physiological health and ecological stability of aquatic species, frequently compromising immune defenses and elevating mortality rates. This study was conducted to elucidate the non-specific immune responses induced by Pallisentis (Neosentis) celatus infection in Monopterus albus, with a focus on intestinal histopathology and transcriptome gene expression. A histopathological examination revealed minor alterations in intestinal villi under low-level infection. A transcriptome analysis, performed using Illumina sequencing technology, identified 347 upregulated and 298 downregulated genes involved in critical biological pathways, such as lipid metabolism, immune responses, and the regulation of inflammatory processes. GO and KEGG analyses indicated the upregulation of immune-related pathways, including the RIG-I-like and IL-17 signaling pathways, highlighting a robust intestinal immune response. Conversely, the complement pathway was found to be downregulated, with significant suppression of C9, suggesting that the parasite may engage in immune evasion. Fluorescein-labeled C9 antibody assays confirmed reduced complement C9 levels in the infected tissues. A real-time PCR analysis identified the differential expression of eight genes, including C5, maats1, CFI, and gmnc, which were consistent with the sequencing results. These findings suggest that Pallisentis (Neosentis) celatus infection compromises intestinal health, induces inflammation, and activates non-specific immune responses in Monopterus albus. However, Pallisentis (Neosentis) celatus appears to evade the host immune response by suppressing the activation of complement components, thereby facilitating its reproductive parasitism.

Real-time lettuce-weed localization and weed severity classification based on lightweight YOLO convolutional neural networks for intelligent intra-row weed control - Rui Hu; Wen-Hao Su; Jia-Le Li; Yankun Peng (Computers and Electronics in Agriculture, 2024)

Ancient genomic time transect unravels the population dynamics of Neolithic middle Yellow River farmers - Shiwei Li; Rui Wang; Hao Ma; Zheng Tu; Limin Qiu; Haodong Chen; Li Jiang; Yuezu Geng; Hai Liu; Jifeng Wang; Qu Shen; Li Jin; et al. (Science Bulletin, 2024)

Effects of 12-year cropping systems and tillage practices on crop yield and carbon trade-off in dryland Loess Plateau - Xingyu Guo; Hao Wang; Naeem Ahmad; Rui Wang; Xiaoli Wang; Jun Li (Field Crops Research, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Long-term escape behavior and release mechanism of organic emissions from asphalt materials - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Rui Li; Gengren Hao (Science of The Total Environment, 2024)

Numerical study on the hydrodynamic performance of a high-speed taxiing fuselage: Investigation on the affecting factors in the numerical simulation - Rui Deng; Hang Ren; Hao Li; Sichong Huang; Tiecheng Wu (Ocean Engineering, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Enhanced oxidative stability and quality of chilled mirror carp fillet using an antioxidant film of chitosan/clove essential oil nanoemulsion - Ying Li; Litong Rui; Hao Zhang; Xiufang Xia (Food Bioscience, 2024)

Quantitative evaluation method for post-earthquake functionality loss of pedestrian flow pathways within a complex building using evacuation and rescue simulation - Zhao-Long Shi; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Han Zhang; Rui Wang (Engineering Structures, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Activation technology of steel slag for concrete exposed to plateau climate: a state-of-the-art review - Wei Deng; Rui Xiong; Xinming Zhai; Kai Huang; Liding Li; Youjie Zong; Haoyu Wang; Jianliang Zhai; Hao Lai; Nan Mao; Changchun Shi; Fuyang Lu (Environmental Science and Pollution Research, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Amphibole fractionation as a key driver for oxidation of magmas in convergent margins - Chen-Hao Luo; Rui Wang; Oliver Nebel; Qi-Wei Li (Earth and Planetary Science Letters, 2024)

A multifunctional barium-modified geopolymer foam for the efficient and flexible treatment of high-sulfate coal mine drainage - Xuhao Zhang; Xiao Zhang; Minghui Ma; Rui Cheng; Chenglong Hao; Li Zhang; Jiaqi Zhang (Chemical Engineering Journal, 2024)

Cu-substituted Na0.75Ni0.17Cu0.08Mn0.75O2 cathode with suppressing P2-O2 phase transition and air-stable for high-performance sodium-ion batteries - Guodong Hao; Shao-hua Luo; Pengyu Li; Ge Wang; Wei Zhao; Rui Huang; Haoran Zang; Jiachen Wang; Lixiong Qian (Chemical Engineering Journal, 2024)

Wearable hydrogel-based health monitoring systems: A new paradigm for health monitoring? - Xintao Wang; Haixia Ji; Li Gao; Rui Hao; Ying Shi; Junyan Yang; Yuan Hao; Jiahui Chen (Chemical Engineering Journal, 2024)

Mutations in wheat TaAPA2 gene result in pleiotropic effects on plant architecture - Shengsheng Bai; Guiping Wang; Rui Song; Yanna Liu; Lei Hua; Jinwei Yang; Lijun Zhang; Shams ur Rehman; Xiaohua Hao; Lifeng Hou; Chaozhong Zhang; Hongna Li; et al. (Science China Life Sciences, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Identification of key genes involved in lignin and flavonoid accumulation during Tilia tuan seed maturation - Lei Liu; Cui Long; Xuri Hao; Rui Zhang; Chenqi Li; Yuepeng Song (Plant Cell Reports, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Genetic affinity of cave burial and Hmong-Mien populations in Guangxi inferred from ancient genomes - Jianxin Guo; Haifeng He; Guangmao Xie; Le Tao; Xi Mai; Kongyang Zhu; Qiusheng Qin; Xiaomin Yang; Ying Xie; Rui Wang; Hao Ma; Jing Zhao; et al. (Archaeological and Anthropological Sciences, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

An ontology-driven method for urban building energy modeling - Rui Ma; Qi Li; Botao Zhang; Hao Huang; Chendi Yang (Sustainable Cities and Society, 2024)

Destabilization of a model O/W/O double emulsion: From bulk to interface - Zijian Zhi; Hao Li; Indi Geurs; Benny Lewille; Rui Liu; Paul Van der Meeren; Koen Dewettinck; Filip van Bockstaele (Food Chemistry, 2024)

Fish skin mucosal surface becomes a barrier of antibiotic resistance genes under apramycin exposure - Wenpeng Li; Xiaohan Zhang; Xiaohan Hao; Rui Xin; Ying Zhang; Yongzheng Ma; Zhiguang Niu (Environmental Research, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

MOF derived highly dispersed bimetallic Fe-Ni nitrogen-doped carbon for enhanced peroxymonosulfate activation and tetracycline degradation - Lingyun Jing; Shasha Liu; Tong Wang; Zeqiang Zhang; Xia Zhao; Zhili Sun; Pengbo Hao; Yeqiang Hu; Wenhan Yang; Rui Quan; Xinyong Li; Dongnian Zhang; et al. (Journal of Environmental Chemical Engineering, 2024)

Developing a combined rotating and air-circulating system for improving radio frequency heating uniformity and controlling Aspergillus in almond kernels - Rui Li; Yu Gao; Junjie Zheng; Mengge Li; Yujun Hao; Longlong Jiang; Shunqin Bai; Dingting Zhou; Juanjuan Xu; Xiaoxi Kou; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

A novel MnCoOx@TiO2 double–wall nanocages derived from Prussian blue analogue for NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Fuel, 2024)

Effects of plastic film mulching on yield, water use efficiency, and nitrogen use efficiency of different crops in China: A meta-analysis - Tiantian Huang; Qianxiang Wu; Yangyang Yuan; Xintong Zhang; Ruiqi Sun; Rui Hao; Xiaohua Yang; Congfeng Li; Xiaoliang Qin; Fangqi Song; Charles O. Joseph; Wen Wang; et al. (Field Crops Research, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Influence of building spatial patterns on wind environment and air pollution dispersion inside an industrial park based on CFD simulation - Qiang Zhao; Rui Li; Kaifa Cao; Mingjian Yi; Hao Liu (Environmental Monitoring and Assessment, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

An organic acid-alkali coordinately regulated liquid electrolyte enables stable cycling of high-voltage proton battery - Huige Ma; Mingsheng Yang; Rui Li; Yan Wang; Liping Zheng; Xiaoming Jing; Yuxing Hao; Yujie Dai; Jiefeng Gao; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Towards energy conservation and carbon reduction for wastewater treatment processes: A review of carbon-neutral anaerobic biotechnologies - Xinzheng Zhang; Tianwei Hao; Tao Zhang; Yong Hu; Rui Lu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Dual stabilization of O/W/O double emulsions by proteins: An interfacial perspective - Zijian Zhi; Hao Li; Indi Geurs; Benny Lewille; Rui Liu; Paul Van der Meeren; Koen Dewettinck; Filip van Bockstaele (Food Hydrocolloids, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Investigation of the intrinsic characteristics of two lock-in regions in a 10:1 π-shaped deck - Jiaying Wang; Feng Wang; Rui He; Jiawu Li; Jianming Hao; Jiupeng Zhang; Xiaoming Huang (Ocean Engineering, 2024)

Towards carbon-neutral biotechnologies for rural wastewater: A review of current treatment processes and future perspectives - Xinzheng Zhang; Guangyi Ma; Tao Chen; Churen Yan; Yiheng Chen; Qinye Wang; Xinyu Peng; Wenjie Xu; Tianwei Hao; Tao Zhang; Rui Lu; Dapeng Li; et al. (Journal of Water Process Engineering, 2024)

The promotion effect of Pr doping on the catalytic performance of MnCeOx catalysts for low-temperature NH3-SCR - Tong Wu; Shan Ren; Rui-tang Guo; Chu-fan Li; Yi-hao You; Shi-yi Guo; Wei-guo Pan (Fuel, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Superfast hydrous-molten salt erosion to fabricate large-size self-supported electrodes for industrial-level current OER - Jie Deng; Zhichao Wang; Hao Yang; Rui Jian; Yufeng Zhang; Ping Xia; Wei Liu; Olivier Fontaine; Yachao Zhu; Luming Li; Si Chen (Chemical Engineering Journal, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

The Sailajiazitage volcanic and related rocks in the Tiekelik belt imply a Neoproterozoic seamount accreted to the southern Tarim Craton - Rui Li; Wenjiao Xiao; Qigui Mao; Hao Wang; Miao Sang; Zhou Tan; Songjian Ao; Dongfang Song (Lithos, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Sub-Himalayan Mesozoic-Cenozoic tectonic-stratigraphic properties and deformation features in the western limb of Hazara Kashmir syntaxis, Pakistan - Irshad Hussain; Zuo-Chen Li; Misbah Fida; Jabir Hussain; Wakeel Hussain; Xian-Zhi Pei; Ya-Jie Yang; Meng Wang; Rui-Bao Li; Lei Pei; Hao Lin (Arabian Journal of Geosciences, 2024)

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Mitigating abortion risk of synthetic musk-contained body wash in pregnant women: Risk assessment and mechanism analysis - Xixi Li; Rui Li; Yong Niu; Meijin Du; Hao Yang; Di Liu (Environmental Pollution, 2023)

Calibration of the carbonate clumped isotope thermometer of land snail shells - Rui Bao; Xuefen Sheng; Chenglong Li; Can Cui; Hao Yan; Junfeng Ji; Jun Chen (Chemical Geology, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Genome resequencing reveals the population structure and genetic diversity of almond in Xinjiang, China - Pengyu Wu; Dong Li; Rui Zhuang; Hao Zuo; Zhiyong Pan; Bo Yang; Chongzhi Xu (Genetic Resources and Crop Evolution, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Reversing seasonality of Southern Hemisphere Annular Mode trend in the 21st century - Fei Zheng; Xiaoning Liu; Hao Wang; Yuxun Li; Rui Wang; Shuailei Yao; Wenjie Dong (International Journal of Climatology, 2023)
The Southern Hemisphere Annular Mode (SAM) is the dominant mode of atmospheric circulation in the Southern Hemisphere extratropical region. In the late 20th century, the SAM underwent a remarkable positive trend, with the strongest trend occurring in austral summer because of Antarctic ozone depletion. In this study, we quantitatively explore changes in the seasonality of the SAM trend under the background of ozone recovery. As expected, accompanied by ozone recovery since 2001, the summer SAM trend has decreased, thus reducing the seasonal difference in the SAM trend between summer and winter. However, what was not expected and found in this study is that the winter SAM has meanwhile shown an increasing positive trend in the early 21st century, which further reverses the seasonality of the SAM trend, leading to a stronger trend in winter rather than summer, which is different from the seasonality in the late 20th century. The reason underlying the winter SAM changes is explored from the perspective of natural variability. Winter SAM exhibits clear multidecadal variability, and the recent increasing trend is a part of multidecadal oscillation. The multidecadal variability of winter SAM may partly originate from the Atlantic Multidecadal Oscillation. The seasonality of linear trend in extratropical surface climate also exhibits reversing characteristics since 2001. In the early 21st century, the acceleration of westerlies and the strengthening of Amundsen Sea Low are stronger in winter, reversing the previous seasonality in the late 20th century, in which the acceleration of westerlies and the strengthening of Amundsen Sea Low is stronger in summer.

Aluminum soap nanoparticles-lignin powder form phase-selective gelator as an efficient sorbent for oils/water separation - Suwan Cui; Bohao Qi; Hao Liu; Xiaojun Sun; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Mutai Bao (Chemosphere, 2023)

Thermokarst lake susceptibility assessment using machine learning models in permafrost landscapes of the Arctic - Rui Wang; Lanlan Guo; Yuting Yang; Hao Zheng; Hong Jia; Baijian Diao; Hang Li; Jifu Liu (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

On sediment incipient motion of marine cohesive sediments with different bulk densities - Shouqian Li; Mingcheng Zhu; Wei Huang; Hao Zhu; Rui Zhang; Yongjun Lu (Geomorphology, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Multi-layer feature fusion for hyperspectral image classification - Siyuan Hao; Rui Li; Min Zhang; Yuanxin Ye (International Journal of Remote Sensing, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Ordovician to Triassic episodic growth of the Dananhu arc, Eastern Tianshan (NW China) - Qigui Mao; Wenjiao Xiao; Songjian Ao; Brian F. Windley; Dongfang Song; Miao Sang; Zhou Tan; Hao Wang; Rui Li (International Geology Review, 2023)

Dietary acetate promotes growth and nutrients deposition in Nile tilapia (Oreochromis niloticus) through increasing acetyl-CoA-triggered energy production - Wen-Hao Zhou; Samwel M. Limbu; Yuan Luo; Rui-Xin Li; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Enhanced nitrogen removal in a pilot-scale AOA-SBFASR system treating municipal wastewater: Process efficiency, microbial community and nitrogen metabolic pathways - Zhi-li Du; Shao-bin Huang; Rui-jian Zhang; Yong-qing Zhang; Hao-tao Dong; Guang-hua Wang; Zhi-min Sun (Journal of Water Process Engineering, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Melt-blown fiber felt for efficient all-weather recovery of viscous oil spills by Joule heating and photothermal effect - Bohao Qi; Nuo Wang; Xin Hu; Suwan Cui; Hao Liu; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Yang Li; Mutai Bao (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Sustainable production of eco-friendly rubberized asphalt binders through chemically crosslinking with polymer modifier - Naipeng Tang; Chenyang Xue; Gengren Hao; Weidong Huang; Hongzhou Zhu; Rui Li (Journal of Cleaner Production, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

The role of trifluoroacetic acid in new particle formation from methanesulfonic acid-methylamine - Yue Hu; Shasha Chen; Shasha Ye; Shuqin Wei; Biwu Chu; Rui Wang; Hao Li; Tianlei Zhang (Atmospheric Environment, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Impact of nitrogen addition on single and mixed tree leaf litter decomposition depends on N forms in subtropical China - Pan-Pan Wu; Zao Zhang; Rui Li; Jing-Hao Ji; Rong Mao (Applied Soil Ecology, 2023)

Research on the source-detector variance reduction method based on the AIS adjoint Monte Carlo method - Yisheng Hao; Rui Qiu; Zhen Wu; Shenshen Gao; Hui Zhang; Junli Li (Annals of Nuclear Energy, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Predictive value of serum proteomic biomarkers for noise-induced hearing loss - Yuqiang Lun; Jiawei Chen; Peiheng Lu; Hao Yuan; Pengwei Ma; Weilong Wang; Rui Liang; Siyu Li; Wei Gao; Xuerui Ding; Zi Wang; Jianing Guo; et al. (Environmental Science and Pollution Research, 2023)

Recent advances in core-shell structured catalysts for low-temperature NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Chemosphere, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Experimental study on low-frequency flow noise at the stern of a surface vessel induced by pulsating pressure - Rui Deng; Zhenpu Yan; Xiang Yu; Hao Li; Hailong Liu; Tiecheng Wu (Ocean Engineering, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

The Regulation of the AMPK/mTOR Axis Mitigates Tendon Stem/Progenitor Cell Senescence and Delays Tendon Aging - Guangchun Dai; Yingjuan Li; Ming Zhang; Panpan Lu; Yuanwei Zhang; Hao Wang; Liu Shi; Mumin Cao; Renwang Shen; Yunfeng Rui (Stem Cell Reviews and Reports, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Lithospheric controls on the formation of the Qilian Shan plateau: Evidence from apatite (U Th)/He and cosmogenic 21Ne results in the Central Qilian Shan - Yan Ma; Jianzhang Pang; Dewen Zheng; Huiping Zhang; Jingxing Yu; Chaopeng Li; Rui Zhang; Yuqi Hao; Ying Wang; Ying Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Enhanced biological stabilization of metal-chelant complexes in the chelator-washed soils by sulfate-reducing bacteria - Guixiang Zhang; Yu Gao; Rui Ren; Xiaofang Guo; Baoshan Xing; Yang Li; Zheyun Zhang; Hao Wu (Journal of Soils and Sediments, 2023)

Large-scale characteristics of thermokarst lakes across the source area of the Yellow River on the Qinghai-Tibetan Plateau - Wen-hui Liu; Guang-hao Zhou; Hai-rui Liu; Qing-peng Li; Chang-wei Xie; Qing Li; Jian-yun Zhao; Qi Zhang (Journal of Mountain Science, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Plant litter strengthens positive biodiversity–ecosystem functioning relationships over time - Wei-Ping Zhang; Dario Fornara; Hao Yang; Rui-Peng Yu; Ragan M. Callaway; Long Li (Trends in Ecology & Evolution, 2023)

High magnesian schist, granitic gneiss, amphibolite and monzogneiss in the eastern Ama Drime Massif in South Tibet (China): A rifted Paleoproterozoic arc fringed the western Columbia supercontinent? - Rui Li; Wenjiao Xiao; Qigui Mao; Ji'en Zhang; Songjian Ao; Dongfang Song; Zhou Tan; Hao Wang; Saunak Bhandari (Precambrian Research, 2023)

Seismic damage characteristics and evaluation of aboveground-underground coupled structures - Gang Li; Han Zhang; Rui Wang; Zhi-Qian Dong; Ding-Hao Yu (Engineering Structures, 2023)

Hybrid plasma-thermal system for methane conversion to ethylene and hydrogen - Rui Liu; Yingzi Hao; Tong Wang; Li Wang; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

High-grade complexes record the Late Permian-Middle Triassic arc metamorphism in the southernmost Altaids: Implications for the final closure of the Paleo-Asian Ocean - Hao Wang; Wenjiao Xiao; Rui Li; Hongxu Chen; Zhou Tan; Qigui Mao; Mengyan Shi (Lithos, 2023)

Multi-model analysis of historical runoff changes in the Lancang-Mekong River Basin – Characteristics and uncertainties - Yuxin Li; Aifang Chen; Ganquan Mao; Penghan Chen; Hao Huang; Hong Yang; Zifeng Wang; Kai Wang; He Chen; Ying Meng; Rui Zhong; Pengfei Wang; et al. (Journal of Hydrology, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Discovery of Neoproterozoic adakitic rocks in the Eastern Tianshan (NW China) of the southern Altaids - Meng Wang; Qigui Mao; Wenjiao Xiao; He Yang; Hao Wang; Rui Li (International Journal of Earth Sciences, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Variability of fuel consumption and CO2 emissions of a gasoline passenger car under multiple in-laboratory and on-road testing conditions - Boya Zhou; Liqiang He; Shijian Zhang; Rui Wang; Luowei Zhang; Mengliang Li; Yu Liu; Shaojun Zhang; Ye Wu; Jiming Hao (Journal of Environmental Sciences, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Dietary sodium acetate improves high-fat diet utilization through promoting differential nutrients metabolism between liver and muscle in Nile tilapia (Oreochromis niloticus) - Wen-Hao Zhou; Samwel M. Limbu; Rui-Xin Li; Yuan Luo; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

How seasonality affects the environmental performance of fresh appetite: Insights from cherry consumption in China - Xin Xiong; Junyi Shen; Yan Hao; Lixiao Zhang; Rui Zhao; Shoujuan Tang; Xinqing Li; Zhimin Shi (Journal of Environmental Management, 2023)

Novel polysaccharide from Panax notoginseng with immunoregulation and prebiotic effects - Hui-Rong Yang; Xue Li; Hao Liu; Dong-Rui Zhao; Ying-Jie Zeng (Food Bioscience, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

Orbital and Millennial-Scale Climate Variability over the Past 76 ka in the Western Tarim Basin, Northwest China - Rui Zhang; Qiuzhen Yin; Weihua Nai; Zhixiang Wang; Hao Lu; Chunju Huang; Yansheng Gu; Lin Li; Yusong Wang; Linjing Liu (Journal of Earth Science, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Fungal polyketides from a rhizospheric soil-derived Penicillium sp. YUD17004 associated with Gastrodia elata - Hong-Tao Li; Rui-Ning Yang; Tao Liu; Fei Xie; Hao-Jie Duan; Dan-Dan Xia; Hao Zhou; Zhong-Tao Ding (Phytochemistry, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Enhancing structural and cycle stability of Prussian blue cathode materials for calcium-ion batteries by introducing divalent Fe - Chong-Yu Du; Zi-Hao Zhang; Xun-Lu Li; Rui-Jie Luo; Cui Ma; Jian Bao; Jie Zeng; Xuan Xu; Fei Wang; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Characterization of a Hyaluronidase-Producing Bacillus sp. CQMU-D Isolated from Soil - Lu Wang; Qianqian Liu; Rui Hao; Jing Xiong; Junxing Li; Yanan Guo; Lu He; Zeng Tu (Current Microbiology, 2022)

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

Influence of different inoculation densities of black soldier fly larvae (Hermetia illucens) on heavy metal immobilization in swine manure - Dongmei Jiang; Kunhong Jiang; Rui Li; Liangbin Zhao; Zile Liu; Bangjie Xiong; Du Jin; Xiaoxia Hao; Li Zhu; Bo Kang; Lin Bai (Environmental Science and Pollution Research, 2022)

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Laboratory and centrifugal model tests on failure mechanism of canal slopes under cyclic action of wetting–drying - Rui Zhu; Ying-hao Huang; Chen Zhang; Wan-li Guo; Hao Chen (European Journal of Environmental and Civil Engineering, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Spermatogonia From Cryopreserved Testes of Critically Endangered Chinese Sturgeon Efficiently Colonized and Preferentially Proliferated in the Recipient Gonads of Yangtze Sturgeon - Huan Ye; Yutaka Takeuchi; Hao Du; Huamei Yue; Rui Ruan; Chuangju Li; Qiwei Wei (Marine Biotechnology, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Risk assessment of non-point source pollution based on landscape pattern in the Hanjiang River basin, China - Yi-wen Liu; Jia-ke Li; Jun Xia; Gai-rui Hao; Fang-Yenn Teo (Environmental Science and Pollution Research, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Ectobacillus aegiceratis sp. nov., a novel bacterium isolated from branch of Aegiceras corniculatum - Xiao-Hui Chen; Xiao-Rui Yan; Zi-Hao Huang; Ming-Sheng Chen; Li Tuo (Antonie van Leeuwenhoek, 2021)

Jiella mangrovi sp. nov., a novel endophytic bacterium isolated from leaf of Rhizophora stylosa - Ming-Sheng Chen; Fei-Na Li; Xiao-Hui Chen; Zi-Hao Huang; Xiao-Rui Yan; Li Tuo (Antonie van Leeuwenhoek, 2021)

Light and high-strength structure inspired by the characteristics of double-nutrient foramens in intertarsal joint of ostrich - Rui Zhang; Chengjin Wang; Shichao Fan; Dong Li; Hao Pang; Lei Ling; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Silurian to early Permian slab melting and crustal growth in the southern Altaids: insights from adakites and associated mineral deposits in the Dananhu arc, Eastern Tianshan, NW China - Qigui Mao; Songjian Ao; Dongfang Song; Wenjiao Xiao; Brian F. Windley; Miao Sang; Zhou Tan; Hao Wang; Rui Li (International Journal of Earth Sciences, 2021)

Phycicoccus avicenniae sp. nov., a novel endophytic actinomycete isolated from a branch of Avicennia mariana - Ming-Sheng Chen; Xiao-Hui Chen; Zi-Hao Huang; Xiao-Rui Yan; Li Tuo (Antonie van Leeuwenhoek, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Overexpression of MdPHR1 Enhanced Tolerance to Phosphorus Deficiency by Increasing MdPAP10 Transcription in Apple (Malus × Domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Journal of Plant Growth Regulation, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

3D DEM analysis on tractive trafficability of a lunar rover wheel with bionic wheel lugs - Hao Pang; Rui Zhang; Ping Ge; Fang Liu; Chengjin Wang; Wenchao Dong; Tao Li; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Different physiological responses of C3 and C4 plants to nanomaterials - Tonghao Bai; Peng Zhang; Zhiling Guo; Andrew J. Chetwynd; Mei Zhang; Muhammad Adeel; Mingshu Li; Kerui Guo; Ruize Gao; Jianwei Li; Yi Hao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Design of the bionic wheel surface based on the friction characteristics of ostrich planta - Hao Pang; Hua Zhang; Rui Zhang; Wenchao Dong; Tao Li; Songsong Ma; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

Partial recovery of disturbed V-J pairing profiles of T-cell receptor in people living with HIV receiving long-term antiretroviral therapy - Guoli Li; Jiarui Li; Henghui Zhang; Yu Zhang; Di Liu; Yu Hao; Junyan Han; Juan Du; Liuluan Zhu; Yongqin Zeng; Bei Li; Rui Li; et al. (Science China Life Sciences, 2021)

Identification and expression analysis of caffeoyl-coenzyme A O-methyltransferase family genes related to lignin biosynthesis in tea plant (Camellia sinensis) - Shi-Jia Lin; Ya-Zhuo Yang; Rui-Min Teng; Hao Liu; Hui Li; Jing Zhuang (Protoplasma, 2021)

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Quantitative assessment of non-point source pollution load of PN/PP based on RUSLE model: a case study in Beiluo River Basin in China - Gai-rui Hao; Jia-ke Li; Shu Li; Kang-bin Li; Zi-hang Zhang; Huai-en Li (Environmental Science and Pollution Research, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

Role of Chromatin Remodeling Genes and TETs in the Development of Human Midbrain Dopaminergic Neurons - Li Xiang; Guobin Huang; Wenjing Shu; Chunli Gong; Nan Cao; Rui Chen; Jixi Li; Hao Lu; Gaofeng Jiang (Stem Cell Reviews and Reports, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Bionic design in anti-bending and lightweight tube based on the tarsometatarsus of ostrich - Rui Zhang; Hao Pang; Dianlei Han; Shuliang Xue; Lei Jiang; Dong Li; Lige Wen; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Molecular cloning and functional characterization of the CEP RECEPTOR 1 gene MdCEPR1 of Apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

PDGFRβ-targeted TRAIL specifically induces apoptosis of activated hepatic stellate cells and ameliorates liver fibrosis - Rui Li; Zhao Li; Yanru Feng; Hao Yang; Qiuxiao Shi; Ze Tao; Jingqiu Cheng; Xiaofeng Lu (Apoptosis, 2020)

Improvement and application research of the SRM in alpine regions - Gai-rui Hao; Jia-ke Li; Kang-bin Li; Kang Huang; Jia-bao Song; Huai-en Li (Environmental Science and Pollution Research, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

Downregulation of AIF-2 Inhibits Proliferation, Migration, and Invasion of Human Glioma Cells via Mitochondrial Dysfunction - Wei Chen; Hao Liu; Tuo Wang; Gang Bao; Ning Wang; Rui-Chun Li (Journal of Molecular Neuroscience, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Antioxidant defense against rust infection in the leaf tissue of Malus crabapple - Yudan Duan; Suxiao Hao; Rui Luo; Yanfen Lu; Ge Li; Jie Zhang; Ji Tian; Yuncong Yao (Acta Physiologiae Plantarum, 2019)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Genome-wide analysis and identification of the SMXL gene family in apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Tree Genetics & Genomes, 2018)

Specific effects of neuregulin-1β on the communication between DRG neurons and skeletal muscle cells in vitro - Menglin Cong; Jianmin Li; Yuan Qiao; Rui Jing; Hao Li; Zhenzhong Li (Journal of Muscle Research and Cell Motility, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Profiling methyl jasmonate-responsive transcriptome for understanding induced systemic resistance in whitebark pine (Pinus albicaulis) - Jun-Jun Liu; Holly Williams; Xiao Rui Li; Anna W. Schoettle; Richard A. Sniezko; Michael Murray; Arezoo Zamany; Gary Roke; Hao Chen (Plant Molecular Biology, 2017)

Identification of the SRO gene family in apples (Malus×domestica) with a functional characterization of MdRCD1 - Haohao Li; Rui Li; Fengjia Qu; Jifang Yao; Yujin Hao; Xiaofei Wang; Chunxiang You (Tree Genetics & Genomes, 2017)

Characterization of angiotensin-І converting enzyme inhibiting peptide from Venerupis philippinarum with nano-liquid chromatography in combination with orbitrap mass spectrum detection and molecular docking - Lei Shi; Tizhi Wu; Naijuan Sheng; Li Yang; Qian Wang; Rui Liu; Hao Wu (Journal of Ocean University of China, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

A new cell line derived from embryonic tissues of Holotrichia parallela (Coleoptera:Scarabaeidae) - Miao-Miao Li; Gui-Ling Zheng; Rui Su; Fang-Hao Wan; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Molecular dynamics-based self-organizing molecular field analysis on 3-amino-6-arylpyrazines as the ataxia telangiectasia mutated and Rad3 related (ATR) protein kinase inhibitors - Hao Luo; Jianyou Shi; Lufei Lu; Feng Wu; Meng Zhou; Xueyan Hou; Wenjuan Zhang; Zhengyu Ding; Rui Li (Medicinal Chemistry Research, 2014)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Magma mixing revealed from in situ zircon U–Pb–Hf isotope analysis of the Muhuguan granitoid pluton, eastern Qinling Orogen, China: implications for late Mesozoic tectonic evolution - Rui Liu; Jian-Wei Li; Shi-Jian Bi; Hao Hu; Mi Chen (International Journal of Earth Sciences, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Effects of grazing on CO2 balance in a semiarid steppe: field observations and modeling - Xiaoming Kang; Yanbin Hao; Xiaoyong Cui; Huai Chen; Changsheng Li; Yichao Rui; Jianqing Tian; Paul Kardol; Lei Zhong; Jinzhi Wang; Yanfen Wang (Journal of Soils and Sediments, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Stratigraphic architecture and computer modelling of carbonate platform margin, late ordovician Lianglitage formation, Central Tarim Basin - Hao Li; Changsong Lin; Yanmei Zhang; Rongxi Zhang; Zhifeng Rui; Lili Huang (Journal of Earth Science, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Implication of genetic variants near TMEM18, BCDIN3D/FAIM2, and MC4R with coronary artery disease and obesity in Chinese: a angiography-based study - Hao Huang; Zhi Zeng; Li Zhang; Rui Liu; Xian Li; Ou Qiang; Yucheng Chen (Molecular Biology Reports, 2012)

Modeling impacts of climate change on carbon dynamics in a steppe ecosystem in Inner Mongolia, China - Xiaoming Kang; Yanbin Hao; Changsheng Li; Xiaoyong Cui; Jinzhi Wang; Yichao Rui; Haishan Niu; Yanfen Wang (Journal of Soils and Sediments, 2011)

Effect of host plants on development and reproduction of Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Rui-Ting Ju; Feng Wang; Fang-Hao Wan; Bo Li (Journal of Pest Science, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

A stand dynamic model for red pine plantations with different initial densities - Shusheng Li; Qingyu Hao; Edwin Swift; Charles P.-A. Bourque; Fan-Rui Meng (New Forests, 2011)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

A Study of Conservation Genetics in Cupressus chengiana, an Endangered Endemic of China, Using ISSR Markers - Bingqing Hao; Wang Li; Mu Linchun; Yao Li; Zhang Rui; Tang Mingxia; Bao Weikai (Biochemical Genetics, 2006)